2015
DOI: 10.5695/jkise.2015.48.5.194
|View full text |Cite
|
Sign up to set email alerts
|

A Blade-Abrading Method for Surface Pretreatment of Mg Alloys

Abstract: A blade-abrading method was newly developed for the preparation of clean Mg alloy surface and reported for the first time in detail in this paper. The blade-abrading method includes abrading of the Mg alloy surface with a sharp blade or knife to remove the surface oxide and contaminants on the skin of Mg alloys mechanically, thereby providing very clean surface of Mg alloys. The clean surface prepared by the blade-abrading method in the air was found to be covered with thin and dense air-formed oxide films. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The SiC paper-abraded specimen surface was abraded finally by a blade to prepare smooth and clean surface by removing the surface oxide and contaminants for improved adhesion with a masking tape, according to the same specimen preparation method as presented in a previous paper [27]. Total exposed area of the specimen, including both sides and edges, was 10 cm…”
Section: Methodsmentioning
confidence: 99%
“…The SiC paper-abraded specimen surface was abraded finally by a blade to prepare smooth and clean surface by removing the surface oxide and contaminants for improved adhesion with a masking tape, according to the same specimen preparation method as presented in a previous paper [27]. Total exposed area of the specimen, including both sides and edges, was 10 cm…”
Section: Methodsmentioning
confidence: 99%
“…The samples were abraded using SiC abrasive papers successively from #220 up to # 2000 grit with ethanol. The SiC paper-abraded specimen surface was finally abraded by pressing and moving of a sharp blade on the Mg alloy surface and then cleaned by compressed air blowing to remove the surface residuals [13]. The samples were masked with a tape to leave an exposure area of 60 cm 2 (6 × 5 cm × 2 sides).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the deposition and the adhesion of the E-paint on Mg alloys could be also different from those of conventional metals. There are some concerns when E-painting process is applied to bare Mg alloys [9,10] can be corroded rapidly in E-painting solutions; (2) Mg rapidly can form loosely bonded and porous oxide/hydroxide films on the surface, which may hinder successive electrodeposition or reduce the adhesion of the E-paint layer [11,12,13]; and (3) Gas evolution which could result in the formation of pores in the E-paint layer [12]. Some studies have been reported the effect pretreatments on the adhesion and corrosion resistance of E-paint on steel and aluminum alloys [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The alloy plate of 1 mm thickness was cut into 9 × 70 mm size and the edges were abraded with # 400 Sic paper. Clean and smooth surface of the specimen was prepared by using a blade-abrading method [22] and masked using a tape, leaving 10 cm 2 of exposed area. The masked specimen was used for PEO treatment.…”
Section: Methodsmentioning
confidence: 99%